Pengaruh Pengembangan Karir, Kepuasan Kerja Dan Komitmen Organisasi Terhadap Intensi Turnover Karyawan Di Kawasan Industri MM2100 - Wachid Hasyim; Lestari Ayu Jayantika (Universitas Persada Indonesia YAI, 2021)
This study aims to determine the effect of Career Development, Job Satisfaction andOrganizational Commitment on Employee Turnover Intentions. the method used in this studyusing quantitative methods. The sample in this study were employees who worked in theMM2100 Industrial Estate with as many as 100 people. Statistical analysis performedincluded multiple linear regression and hypothesis testing. Based on the results of dataanalysis, it can be concluded that: There is a negative and significant effect of CareerDevelopment on Employee Turnover Intentions. There is a negative and significant effect ofjob satisfaction on employee turnover intentions. There is a negative and significant effect oforganizational commitment on turnover intentions. The value of the coefficient ofdetermination is 0.820, which means that variations in employee turnover intentions in theMM2100 Industrial Estate are influenced by Career Development, Job Satisfaction andOrganizational Commitment by 82%. While the remaining 18% is influenced by othervariables outside the study.